2017
DOI: 10.1016/j.joep.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Measures of individual risk attitudes and portfolio choice: Evidence from pension participants

Abstract: We use a large non-student sample to test how distinct measures of risk-attitudes relate to each other, to demographic characteristics and to real-life risk taking in the financial domain. These measures, namely the Bomb Risk Elicitation Task (BRET), self-reported willingness to take risks in general, the choice in a hypothetical lottery, the score in the Domain Specific Risk-Taking (DOSPERT) scale, appear to be positively correlated and exhibit a certain degree of consistency. Furthermore, a subset is driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
5
16
0
Order By: Relevance
“…These controls are crucial as these variables are known to be related to risk attitudes and the sex and age structures are different among students, novices, and experienced firefighters. Consistently with the literature, we find that risk aversion increases with age (Dohmen et al, 2011;Palsson, 1996;Gurdal et al, 2017). Table 2 The OLS regression on data from all students and firefighters The variable experienced shows that the firefighters with two or more years in the fire rescue service are more 5 risk-seeking than novices.…”
Section: Resultssupporting
confidence: 85%
“…These controls are crucial as these variables are known to be related to risk attitudes and the sex and age structures are different among students, novices, and experienced firefighters. Consistently with the literature, we find that risk aversion increases with age (Dohmen et al, 2011;Palsson, 1996;Gurdal et al, 2017). Table 2 The OLS regression on data from all students and firefighters The variable experienced shows that the firefighters with two or more years in the fire rescue service are more 5 risk-seeking than novices.…”
Section: Resultssupporting
confidence: 85%
“…Barsky et al (1997) utilized responses from hypothetical questions to anticipate real-life risky behaviors, for example holding stocks and found little impact. Generally, willingness to taking risks leads to risky behaviors (Gürdal et al, 2017). Nosić and Weber (2010) concluded that a subjective risk attitude impacts investment in shares positively as supported by Cheng et al (2018).…”
Section: Risk Attitudes and Stock Market Participationmentioning
confidence: 89%
“…That is, the measure of individual risk attitude was changed from the tendency to take or avoid risk across five domains (i.e., ethical, financial, health/safety, recreational, and social) to the tendency to take or avoid risk only in the financial domain (hereinafter labelled financial risk attitude). This alternative measure for individual risk attitude was proposed because there are two different notions in the literature regarding the appropriate way of measuring individual risk attitude (Weber, 2010;Maart-Noelck & Musshoff, 2014;Van Winsen et al, 2016;Gürdal, regression analysis that are used to evaluate the research hypotheses are presented in Table 2. Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the hypotheses, the first hypothesis proposed in this study (H 1 ) predicted that auditors with a smaller tendency to take risk would be more conservative when performing audit tasks. The regressions results reported in Kuzubaþ, & Saltoðlu, 2017). The first notion considers risk attitude as a stable, dispositional characteristic of an individual that is consistent across situations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation